5(m-2)=-(6m-1)

Simple and best practice solution for 5(m-2)=-(6m-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m-2)=-(6m-1) equation:


Simplifying
5(m + -2) = -1(6m + -1)

Reorder the terms:
5(-2 + m) = -1(6m + -1)
(-2 * 5 + m * 5) = -1(6m + -1)
(-10 + 5m) = -1(6m + -1)

Reorder the terms:
-10 + 5m = -1(-1 + 6m)
-10 + 5m = (-1 * -1 + 6m * -1)
-10 + 5m = (1 + -6m)

Solving
-10 + 5m = 1 + -6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6m' to each side of the equation.
-10 + 5m + 6m = 1 + -6m + 6m

Combine like terms: 5m + 6m = 11m
-10 + 11m = 1 + -6m + 6m

Combine like terms: -6m + 6m = 0
-10 + 11m = 1 + 0
-10 + 11m = 1

Add '10' to each side of the equation.
-10 + 10 + 11m = 1 + 10

Combine like terms: -10 + 10 = 0
0 + 11m = 1 + 10
11m = 1 + 10

Combine like terms: 1 + 10 = 11
11m = 11

Divide each side by '11'.
m = 1

Simplifying
m = 1

See similar equations:

| x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 | | (8x+3)(5x+8)=180 | | 3x+9(3x+1)=9x-6 | | 6(4x+3)=138 | | 5x+9i=10-3yi | | 2x+9+9x-8=8x+19 | | 15x-3(6+5x)=-18 | | x*x=16+(x+-4)(x+2) | | 8+6y=7y | | 2x+6=-6-2 | | -4(v+7)=-(1+7v) | | 14.3=-1.4-3d | | x*x=16+(x-4)*(x+4) | | P/g=10 | | 9x-5-6x-2=6x-1 | | -10-9z+10z=-12 | | 5g+2=10-3g-8 | | -5r+5=-6r+2 | | (3x-1)(6x+9)=0 | | (x-4)*(x+4)=486 | | 3.50t+5.50+6t=51 | | d+6=10-3d | | 1-7n-1=-8n | | (x-4)*(x-4)=486 | | 60+60+x-20=360 | | 9x-5-6x-2=6x-7 | | -4n+6n=6n-12 | | 2q-6=3+3q |

Equations solver categories